PENGETAHUAN, PERSEPSI, DAN SIKAP IBU HAMIL TERHADAP KLAIM GIZI KAITANNYA DENGAN KEPUTUSAN PEMBELIAN PRODUK SUSU IBU HAMIL - Damayanti, Rinda; Rimbawan, Rimbawan (Jurnal Gizi dan Pangan, 2016)
The purposes of this research was to analyze the influence of individual characteristics, nutritional knowledge, nutrition claim’s knowledge, perception and attitude on nutrition claim of maternal milk product on purchasing decision. This research used cross sectional study design, on 60 pregnant women that consisted of 30 who have consumed and 30 who didn’t consume maternal milk products. This research was conducted in working area of Public Health Centre Ciampea, Bogor District which was choosen purposively. Dependent variable in this research are individual characteristics, nutritional knowledge, nutrition claim’s knowledge, perception and attitude on nutrition claim, meanwhile independent variable in this research is purchasing decision of maternal milk product. Statistic analysis used in this research were Mann Whitney and logistic regression analysis. Education level, family income, income per capita, and nutrition knowledge of subject who consumed maternal milk product was better than who did not consume maternal milk. The opportunity of purchasing decision on maternal milk product would increase 3,99 times if education level was more than 9 years, 4,18 times when family income was more than Rp 1.500.000 every month, and 3,69 times when index of nutrition claim’s perception was more than 65. This research is intended to increase awareness for understanding nutrition claim on maternal milk products and can help food industry to identify factor that influence purchasing decision on maternal milk products.Keywords: maternal milk product, nutrition claim, pregnant women, purchasing decision